عن الاختصاص في ضبط السوق والنشاط التجاري بين مجلس المنافسة ومصالح وزارة التجارة - حساين, سامية (جامعة الوادي University of Eloued, 2019)
ملخص: يعبّر الضبط في مجال السوق عن تدخل الدولة بواسطة سلطاتها للرقابة على مختلف الأنشطة التي يمارسها المتدخلين في الميدان الاقتصادي، تجسيدا لذلك تدخل المشرع الجزائري بوضح اطر قانونية اهمها الأمر رقم 03-03 المعدل والمتمم المتضمن قانون المنافسة وكذا القانون رقم 04-02 المعدل والمتمم لتنظيم المنافسة في اطار الممارسات التجارية ، من أجل تفعيل هذه القوانين أوكلت مهمة تنظيم المنافسة وضبط السوق لهيئة إدارية مستقلة تسهر على تنظيم الحياة الاقتصادية، تتمثل في مجلس المنافسة، مع العلم ان المهام الموكلة لها كانت قد منحت للهيئة الإدارية المنوط لها في الاصل مهمة الضبط والرقابة والردع والقمع والمتمثلة في السلطة التنفيذية، الممثلة في وزارة التجارة على مستويات مختلفة، فيما قد تطرح مسألة التنازع عن الاختصاص او انها مجرد تقاسم لها وتوزيع من شانه أن يعزز مهمة الضبط الاقتصادي بين الهيئتين. الكلمات المفتاحية : مجلس المنافسة ، الاختصاص، وزارة التجارة ، الرقابة . Abstract: The control in the field of the market expresses the interference of the state by its authorities to control the various activities practiced by the economic actors. In this regard, the Algerian legislator intervenes with legal frameworks, the most important of which is the modified and supplemented order n° 03-03, which includes the competition law, as well as the law n° 04-02 which adjusts and completes the competition regulation within the framework of commercial practices. In order to activate these laws, the task of organizing competition and regulating the market has been entrusted to an independent administrative body that regulates economic life. It is the Competitiveness Council, knowing that these tasks were originally assigned to an administrative authority charged of adjusting, controlling, deterrence and repression, which is the executive authority represented by the Ministry of Commerce at different levels may raise the issue of conflict of jurisdiction or it’s just a sharing and distribution, which would strengthen the mission of economic regulation between the two authorities. key words: the Competitiveness Council. conflict of jurisdiction. the Ministry of Commerce
Keywords: مجلس المنافسة ; الرقابة ; الاختصاص، وزارة التجارة